Detection of Apoptotic Cells in a Rabbit Model with Atherosclerosis-Like Lesions Using the Positron Emission Tomography Radiotracer [F]ML-10 - Fabien Hyafil; Alexy Tran-Dinh; Samuel Burg; Sébastien Leygnac; Liliane Louedec; Milan Milliner; Rana Ben Azzouna; Ayelet Reshef; Miri Ben Ami; Olivier Meilhac; Dominique Le Guludec (Molecular Imaging)
[ 18 F]ML-10 (2-(5-fluoro-pentyl)-2-methylmalonic acid) is a positron emission tomography (PET) radiotracer that accumulates in cells presenting apoptosis-specific membrane alterations. The aim of this study was to test whether [ 18 F]ML-10 allows for the detection of apoptotic cells located in atherosclerotic plaques in rabbits. Atherosclerotic plaques were induced in the aortas of five rabbits, and five additional rabbits were used as controls. Activity in the aortas was quantified in vivo and ex vivo. The localization of [ 18 F]ML-10 to the aortic wall was identified by autoradiography. Average target to background ratios measured in vivo by PET were higher in the aortas of atherosclerotic rabbits compared with those of control rabbits (2.00 ± 0.52 vs 1.22 ± 0.30; p < .05). Differences in [ 18 F]ML-10 uptake between atherosclerotic and control aortas were confirmed ex vivo by PET and gamma counting (23.9 ± 11.2 vs 1.1 ± 2.4 counts/pixel; p <.05; 3.6 ± 2.0 vs 0.05 ± 0.05 % of injected activity/g; p < .05, respectively). Strong correlation was observed between the accumulation of [ 18 F]ML-10 in aortic segments as detected by autoradiography and the number of apoptotic cells on corresponding histologic sections ( r 2 = .75; p < .05). In this study, we found that atherosclerotic plaques rich in apoptotic cells can be detected with [ 18 F]ML-10 and PET.